Student information-seeking behavior in fashion trends of FISIP students at Universitas Bengkulu - Samosir, Fransiska Timoria; Ginting, Richard Togaranta; Santoso, Syarifurohmat Pratama (Jurnal Kajian Informasi dan Perpustakaan, 2023)
Outfit Of The Day (OOTD) fashion information is part of students' daily lives. Searching for online fashion information is often done before making a decision when shopping online. This research aimed to determine the fashion information-seeking behavior of FISIP students, Universitas Bengkulu in following OOTD trends. Research method was quantitative with a survey method through population was 2,731 students from 6 departments and sample of 96 respondents. Research results showed that FISIP students often look for information on fashion and shopping on the Internet. The e-commerce platform Shopee and social media Instagram were the media most often used to find information. Students' information-seeking behavior was categorized as quite good, with a score of 3,16. Women and men only had a slight difference: women more often searched for fashion information on the Internet.The FISIP students often use the Internet to look for information on fashion. Online shopping was the main choice compared to shopping in physical stores directly. The platform most often used to search for fashion information e-commerce was Shopee. Students would buy clothes, shoes and accessories. Students chose online shopping accounts that were most visited and used by buyers online. Before deciding to buy, students paid attention to reviews and ratings from online stores in e-commerce. In conclusion the information-seeking behavior of FISIP students at Universitas Bengkulu is in a good category, as they have gone through stages of information-seeking behavior when looking for information on fashion trends before deciding to buy.